LAND AVAILABILITY AND REQUIREMENT ON ISLAMIC CEMETERY AT KAMPUNG TOKAI, PENDANG - Nur Shazmiera Shamin Sha Bani; Muhamad Azrul Azwan Azman; Norsyazlin Mohd Rosli; Nur Shaffiqa Muhammad Soffian; Aizazi Lutfi Ahmad; Mohd Sabri Mohd Arip (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Nowadays land limitation for Islamic cemetery has become main concern among Muslim community, authority, and Islamic NGOs. Thus, awareness and systematic mitigating these issues are necessary planning. Against these backdrops, the objective of the study is to determine the maximum limit of land availability for Islamic Cemetery by applying planning guideline and the provision of required facilities and utilities. The methodology uses secondary data to analyse and interpret projection data. This study shall be beneficial to the authority in-charge of cemetery management in purpose of references for future requirements and needs. In a hope, this study can give impact in land cemetery planning while enhancing on alternatives approach as the solution for other new cases.